Evaluation of the accuracy of digital and conventional implant-level impression techniques for maxillofacial prosthesis - Mohammad Taghi Baghani; Ammar Neshati; Mehdi Sadafi; Shireen Shidfar (Journal of Family Medicine and Primary Care)
Objectives: This study aims to evaluate the accuracy of digital impression making based on trueness and precision measurements of dental implants placed in maxillofacial lesions to produce Maxillofacial prosthesis substructures. Methods: Two intra-oral scanners (Trios 3 and CS 3700) and one Desktop scanner (open technology) were examined in this study. A Model of a patient with a lesion in the ear region was created as a reference. The reference model was scanned by each scanner 10 times. Standard Tessellation Language files were provided from each scanner and were examined in terms of Trueness and Precision aspects. Results: In Distance 1, in the one-way analysis of variance test, there was a significant difference between the three scanners. The Trios group has less deviation than the Open Technology group (P = 0.015) compared with the CareStream (CS) group that showed more deviation (P < 0.000). There is a statistically significant difference in distance 2 among scanners. The Trios group showed more deviation as compared with the Open Technology group (P < 0.000). While this deviation is not statistically significant compared with the CS group (P = 0.0907). Open Technology Group compared with the CS group also has less deviation in distance 2, which has been statistically significant (P < 0.000). The preparation of a precise model of maxillofacial lesions is still difficult for some Intraoral scanners. Conclusion: There were significant statistical differences in Trueness and Precision among scanners. Used scanners can be applied as an alternative to conventional impression methods.